Management of pain on hallux valgus with percutaneous intra‐articular Pulse‐Dose Radiofrequency. (19th June 2014) - Masala, Salvatore; Fiori, Roberto; Calabria, Eros; Raguso, Mario; de Vivo, Dominique; Cuzzolino, Alessandro; Simonetti, Giovanni
Abstract: Aim: The purpose of our study was to investigate the role of intra‐articular pulse‐dose radiofrequency in management of painful hallux valgus refractory to conservative therapies. Method: Between November 2010 and April 2012, 51 patients (15 male, 36 female) with a median age of 71.4 years were included in our clinical trial. Under fluoroscopic guidance we introduced a 22 gauge 10 cm length cannula by a percutaneous access in the first metatarsophalangeal joint and its tip was placed intra‐articularly. After removing the spindle, a radiofrequency needle with a 5 mm active tip was introduced. The following parameters were used: 1200 pulses at high voltage (45 V) with 20 msec duration followed by 480 msec silent phases. Results: A great reduction in pain intensity was documented at 1 week, 1 month and 3 months after procedures. Pain intensity increased between 5 and 8 months after treatments, so we performed a second procedure in all patients between 7 months and 9 months since the first treatment. Also in this case we obtained a great reduction of pain intensity in the first 3 months after the procedure. Pain intensity returned at preprocedural values after 9 months after second procedure. No complications were observed. Conclusion: Our experience shows pulse‐dose radiofrequency is a safe, repeatable and effective technique for managing patients with symptomatic hallux valgus in the short and medium term. Pulse‐dose radiofrequency may improve pain control and quality of life in patients with hallux valgus refractory to conservative therapies.